Isorhynchophylline Ameliorates Cerebral Ischemia/Reperfusion Injury by Inhibiting CX3CR1-Mediated Microglial Activation and Neuroinflammation - Deng, Yuanyuan; Tan, Ruirong; Li, Fei; Liu, Yuangui; Shi, Jingshan; Gong, Qihai (Frontiers in Pharmacology, 2021)
Reperfusion therapy is an effective way to rescue cerebral ischemic injury, but this therapy also shows the detrimental risk of devastating disorders and death due to the possible inflammatory responses involved in the pathologies. Hence, the therapy of ischemia/reperfusion (I/R) injury is a great challenge currently. Isorhynchophylline (IRN), a tetracyclic oxindole alkaloid extracted from U. rhynchophylla, has previously shown neuroprotective and anti-inflammatory effects in microglial cells. This study systematically investigates the effect of IRN on I/R injury and its underlying mechanism. The effects of IRN on neuronal injury and microglia-mediated inflammatory response were assessed on a rat model with middle cerebral artery occlusion (MCAO) and reperfusion-induced injury. We found that IRN treatment attenuated the infarct volume and improved the neurological function in I/R injury rats. IRN treatment also reduced the neuronal death rate, brain water content, and aquaporin-4 expression in the ischemic penumbra of I/R injury rats’ brain. Besides, IRN treatment could inhibit the following process, including IκB-α degradation, NF-κB p65 activation, and CX3CR1 expression, as well as the microglial activation and inflammatory response. These findings suggested that IRN is a promising candidate to treat the cerebral I/R injury via inhibiting microglia activation and neuroinflammation.